Macroeconomic and Financial Soundness Indicators : An Empirical Investigation - Babihuga, Rita (IMF Working Papers; Working Paper ;, 2007)
This paper analyzes the relationship between selected macroeconomic and financial soundness indicators (FSIs) using a newly assembled panel dataset of FSIs for 96 countries covering the period 1998-2005. The analysis covers key macroeconomic indicators and FSIs of capital adequacy, asset quality and profitability. The paper finds that FSIs fluctuate strongly with both the business cycle and the inflation rate. Short term interest rates and the real exchange rate also emerge as important determinants. There is also a considerable degree of heterogeneity in the relationship between macroeconomic indicators and FSIs across the sample of countries. Several country and industry specific characteristics including country income levels, financial depth, market concentration, and the quality of regulatory supervision are found to be significant in explaining this cross country heterogeneity.